Difference of Red Blood Cell Count (RBC) Levels in Diabetes Mellitus Type II with Ulcers and without Ulcers - Mushlih, Miftahul (Universitas Negeri Surabaya, 2020)
Type II diabetes mellitus (T2DM) is a metabolic disorder that has potential causing ulcer complications. Ulcers occur due to peripheral vascular abnormalities and trauma. The occurrence of ulcers allows differences in the hematology characteristics in sufferers. This study aimed to determine the comparison of the blood picture between T2DM with ulcers and T2DM without ulcers. This was analytical descriptive research using 29 samples (10 T2DM samples with ulcers and 19 T2DM samples without ulcers). A complete blood test was performed using Sysmex Kx-21N hematology analyzer. Data were analyzed using Independent T-test and Mann-Whitney U depends on the normality. Normality was done using Shapiro Wilk (Confident Level: 95%). The results of this study indicated that Red blood cell count (RBC) and Hemoglobin Count (HGB) differ significantly between T2DM with ulcers and T2DM without ulcers (p: 0.012 and 0.006). The identification of HGB levels was highly recommended to get proper treatment in T2DM.